2018
DOI: 10.1007/s00330-018-5580-2
|View full text |Cite
|
Sign up to set email alerts
|

A reality check in transradial access: a single-centre comparison of transradial and transfemoral access for abdominal and peripheral intervention

Abstract: • Transradial access (TRA) is feasible in a variety of peripheral interventions, achieving success in 93.2% of cases. • Access-related complications are comparable between transfemoral access (TFA) and TRA (p = 0.241), but prudence must be taken during TRA as it could be technically challenging. • Procedures performed with TRA tend to have longer fluoroscopy time compared to those performed with TFA (p = 0.033), but the DAPs are comparable (p = 0.186).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The radiation dose and fluoroscopy time remain controversial. Although some studies have claimed increased radiation dose and/or fluoroscopy time during TRA (11,12,21), several studies reported no significant difference in radiation dose or fluoroscopy time between TRA and TFA (8,(13)(14)(15)22).…”
Section: Radiation Dose and Fluoroscopy Timementioning
confidence: 99%
See 2 more Smart Citations
“…The radiation dose and fluoroscopy time remain controversial. Although some studies have claimed increased radiation dose and/or fluoroscopy time during TRA (11,12,21), several studies reported no significant difference in radiation dose or fluoroscopy time between TRA and TFA (8,(13)(14)(15)22).…”
Section: Radiation Dose and Fluoroscopy Timementioning
confidence: 99%
“…Although TFA is the most widely used transarterial chemoembolization (TACE) approach for hepatocellular carcinoma (HCC), a growing number of TACE procedures for HCC via TRA are performed because of the emerging evidence favoring TRA over TFA in recent studies in terms of higher patient satisfaction, lower radiation exposure, and lower complication rates (8,12,28,29).…”
Section: Clinical Applications Transarterial Chemoembolization For Hementioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, the increasing usage of transradial approach has spread to other disciplines. Transradial approach performed by radiologist for abdominal and peripheral intervention has shown less rate of complication but with longer procedural time compared to transfemoral approach (46). Comparison of transradial and transfemoral approach with thombectomy of anterior circulation stroke revealed equivalence in efficacy and efficiency (47).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, radial access (RA) for routine peripheral endovascular procedures has been popularized owing to decreased hemorrhagic complications (Posham et al 2016) as well as improved patient satisfaction and decreased operator radiation dose (Yamada et al 2018). However, not all investigators have found RA superior to traditional FA (Hung et al 2019), and though uncommon, cerebrovascular complications from RA approach are a known risk. Stroke has been reported from peripheral angiography via RA (Al-Hakim et al 2017), and compared to FA, patients undergoing cardiac angiography procedures from RA have been shown to have 2.1 times increased risk of silent stroke (Göksülük et al 2018).…”
Section: Introductionmentioning
confidence: 99%